Fiber dimensions, lignin and cellulose content of various plant materials and their suitability for paper production - Ververis, C.; Georghiou, K.; Christodoulakis, N.; Santas, P.; Santas, R. (Industrial Crops and Products, 2004)
Fiber dimensions and lignin and cellulose content of various highly productive, non-wood plants and agricultural residues were examined to assess their suitability for paper production. Plants like kenaf (Hibiscus cannabinus L.) and giant reed (Arundo donax L.) internodes gave very good derived values, especially slenderness ratio, which is directly comparable to some softwood and most hardwood species. Cotton (Gossypium hirsutum L.) stalks, miscanthus (Miscanthus × giganteus) and switchgrass (Panicum virgatum L.) have shorter fibers resulting to poorer flexibility and Runkel ratios, but still satisfactory slenderness ratios. Finally, fibers from olive tree (Olea europea L.) and almond tree (Prunus dulcis L.) prunings presented relatively short and thick fibers producing the poorest derived values among all the species examined. Fiber dimensions did not differ significantly within each species, when samples from different stalks/branches or different positions (base, middle top) were examined. The only exception were cotton stalks, where those differences did not have any significant effect on fiber derived values. Chemical analysis of the raw plant materials revealed satisfactory levels of α-cellulose content (close to 40%) and Klason lignin content (<30%) compared to those of hardwoods and softwoods. Relatively increased (>25%) lignin content in miscanthus, switchgrass and almond prunings may require additional pulping time and chemical charge compared to those of other non-wood raw materials. Analysis of samples at various heights/lengths of the plant materials showed that lignin and cellulose content depends on tissue maturity, but does not change significantly within each species. © 2003 Elsevier B.V. All rights reserved.
Keywords: Agricultural residues; Arundo donax; Cellulose; cotton fiber; Fiber dimensions; Gossypium hirsutum; Hardwoods; Hibiscus cannabinus; Hirsutum; Internodes; kenaf fiber; Lignin; Lignin and cellulose content; Lignins; Mechanical strength; Miscanthus; Natural fibers; Non-wood plants; Olea europaea; Panicum virgatum; Paper Making; Paper production; Papermaking; Phragmites; Prunus dulcis; Pulp manufacture; Softwoods